In vivo characterization of the role of tissue‐specific translation elongation factor 1A2 in protein synthesis reveals insights into muscle atrophy. (23rd October 2013) - Doig, Jennifer; Griffiths, Lowri A.; Peberdy, David; Dharmasaroja, Permphan; Vera, Maria; Davies, Faith J. C.; Newbery, Helen J.; Brownstein, David; Abbott, Catherine M.
<x xml:space="preserve">Abstract</x> Translation elongation factor 1A2 (eEF1A2), uniquely among translation factors, is expressed specifically in neurons and muscle. eEF1A2‐null mutant wasted mice develop an aggressive, early‐onset form of neurodegeneration, but it is unknown whether the wasting results from denervation of the muscles, or whether the mice have a primary myopathy resulting from loss of translation activity in muscle. We set out to establish the relative contributions of loss of eEF1A2 in the different tissues to this postnatal lethal phenotype. We used tissue‐specific transgenesis to show that correction of eEF1A2 levels in muscle fails to ameliorate the overt phenotypic abnormalities or time of death of wasted mice. Molecular markers of muscle atrophy such as Fbxo32 were dramatically upregulated at the RNA level in wasted mice, both in the presence and in the absence of muscle‐specific expression of eEF1A2, but the degree of upregulation at the protein level was significantly lower in those wasted mice without transgene‐derived expression of eEF1A2 in muscle. This provides the first in vivo confirmation that eEF1A2 plays an important role in translation. In spite of the inability of the nontransgenic wasted mice to upregulate key atrogenes at the protein level in response to denervation to the same degree as their transgenic counterparts, there were no measurable differences between transgenic and nontransgenic wasted mice in terms of weight loss, grip strength, or muscle pathology. This suggests that a compromised ability fully to execute the atrogene pathway in denervated muscle does not affect the process of muscle atrophy in the short term.